2000
DOI: 10.1021/ol991276i
|View full text |Cite
|
Sign up to set email alerts
|

Axially Chiral Amidinium Ions as Inducers of Enantioselectivity in Diels−Alder Reactions

Abstract: [reaction: see text] Enantioselective catalysis of Diels-Alder reactions is mostly achieved by coordinating the dienophile to relatively strong chiral Lewis acids. Here we report on a novel approach employing the hydrogen-bond-mediated association of dienophiles to chiral host molecules. In a reaction forming the steroid skeleton of norgestrel, chiral amidinium ions induce 5:ent-5 ratios of up to 2.5:1. Improved and simplified amidinium catalysts may become interesting candidates to perform stereoselective tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
6

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(46 citation statements)
references
References 6 publications
1
38
0
6
Order By: Relevance
“…Their initial studies, employing achiral amidinium ions derived from palmitic acid, highlighted the importance of non-coordinating counterions, such as the tetrakis(3,5-bis(trifluoromethyl)phenyl)borate (BAr Modest enantioselectivity in the Diels-Alder reaction was achieved by using catalyst 8 (Scheme 11). [52] The possibility that the phenol groups of 8 participate in additional Hbonding contacts with the diketone electrophile was suggested. High enantioselectivity in an amidinium-catalyzed reaction was reported more recently by Johnston and coworkers.…”
Section: Chiral Guanidinium and Amidinium Ionsmentioning
confidence: 99%
“…Their initial studies, employing achiral amidinium ions derived from palmitic acid, highlighted the importance of non-coordinating counterions, such as the tetrakis(3,5-bis(trifluoromethyl)phenyl)borate (BAr Modest enantioselectivity in the Diels-Alder reaction was achieved by using catalyst 8 (Scheme 11). [52] The possibility that the phenol groups of 8 participate in additional Hbonding contacts with the diketone electrophile was suggested. High enantioselectivity in an amidinium-catalyzed reaction was reported more recently by Johnston and coworkers.…”
Section: Chiral Guanidinium and Amidinium Ionsmentioning
confidence: 99%
“…Als Katalysator fungierte hier ein chirales Amidiniumsalz, das die gewünschten Produkte in guten Selektivitäten lieferte. [16] Eine effizientere Methode wurde wenig später von Yamamoto und Nakashima am Beispiel einer Reaktion von Ethylvinylketon mit verschiedensten Dienen beschrieben. [6] In dieser Arbeit wurden erste Versuche mit dem bereits zuvor beschriebenen BP ent-15 a durchgeführt.…”
Section: Metall-liganden Oder Brønsted-säurenunclassified
“…The second metal-free catalysis of Diels-Alder reactions is based on the activation of the dienophile by hydrogen bonding, a form of Brønsted acid catalysis, with a chiral catalyst. To date this approach has been reported to provide only modest successes [Յ50% enantiomeric excess (ee)] (13). In this article, we report the highly enantioselective carbon Diels-Alder reactions (up to 92% ee) catalyzed through hydrogen bonding to an organic catalyst (14).…”
mentioning
confidence: 99%
“…The same group has recently reported highly enantioselective Mannich reactions catalyzed by a similar thiourea catalyst (29,30). In the area of cycloadditions, Göbel and coworkers (13) showed that enantioselective catalysis of Diels-Alder reactions could be achieved through hydrogenbond-mediated association of a dienophile to an axially chiral amidinium ion. Other recent examples of the use of hydrogen bonding are enantioselective Morita-Baylis-Hilman reactions of cyclic enones catalyzed by chiral BINOL derivatives (31), and Michael additions of malonates to nitroolefins catalyzed by functionalized thioureas (32).…”
mentioning
confidence: 99%